PERLINDUNGAN HUKUM TERHADAP HAK ASASI MANUSIA BAGI NARAPIDANA NARKOBA DALAM SISTEM PEMASYARAKATAN PADA RUMAH TAHANAN (RUTAN) SIALANG BUNGKUK PEKANBARU - Luthfia, Naura (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Imprisonment is one of the main forms of punishment served by prisoners based on thejudge's decision, where prisoners are placed in correctional institutions, hereinafterreferred to as LAPAS, which is a place to carry out guidance for prisoners. Or DetentionCenter, hereinafter referred to as RUTAN, is a place where suspects or defendants aredetained during the investigation process. Prisoners' rights are regulated in theprovisions of Article 9 of Law Number 22 of 2022 concerning Corrections. Convicts asconvicts serving prison sentences have rights protected by Human Rights andIndonesian Law, one of which is the provision of remissions.This research aims to determine the legal protection of human rights for drugconvicts in the correctional system at the Siang Bungkuk Pekanbaru detention center(RUTAN) and as information material for the community and parties involved inupholding human rights. This research uses sociological legal research wheresociological legal research is research carried out directly on location or in the field toobtain data to provide a complete and clear picture of the problem being studied. Thepopulation was determined to be 500 narcotics prisoners with a sample of 5 narcoticsprisoners. Based on the research results, it can be seen that in the implementation oflegal protection of human rights for drug convicts in the correctional system at the SiangBungkuk Pekanbaru detention center (RUTAN). The research results show that thereare differences in the implementation of human rights protection for prisoners with LawNumber 22 of 2022 concerning Corrections.The implementation of prisoner's rights at the Sialang Bungkuk DetentionCenter has gone quite well, but the issue of remission has not gone well. Theimplementation of the rights of prisoners in the Sialang Bungkuk Detention Center hasbeen going quite well, especially for the rights contained in Article 9 of Law Number 22of 2022 concerning Corrections as well as human rights which cannot be reduced evenwhile serving a prison sentence have also been implemented. by RTAN SialangBungkuk, however, the prisoners' rights contained in article 10 of Law Number 22 of2022 concerning Corrections regarding the issue of granting remissions are still noteffective due to a lack of socialization by the Rutan, therefore the need for socializationby the Rutan to prisoners.Keywords: Legal Protection, Human Rights, Prisoners.